2020
DOI: 10.1021/acsmedchemlett.9b00508
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Pharmacokinetics of Sulfamides and Guanidines as Potent Human Arginase 1 Inhibitors

Abstract: We designed and synthesized a series of arginase inhibitors as derivatives of the well-known 2-(S)-amino-6boronohexanoic acid (ABH) with basic and neutral side chains in the α-position relative to the amino acid group. In an effort to improve the pharmacokinetic profile of literature examples and retain potent enzymatic activity, sulfamido moieties were introduced to generate hydrogen bond interaction with the aspartic acid residue in the arginase active site. The compounds with basic guanidine-containing side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Here, we have used a novel Arg inhibitor (OAT-1746) that blocks both extracellular and intracellular Arg activity and has pharmacokinetic properties allowing for administration twice daily. 38,64 We have observed that OAT-1746 completely restores T-cell proliferation suppressed by recombinant Arg1 added to the culture media. Arg1 suppressed T-cell proliferation (online supplementary figure 6), but did not suppress cytotoxicity effector functions of T-cells and NK cells (online supplementary figure 9).…”
Section: Discussionmentioning
confidence: 94%
“…Here, we have used a novel Arg inhibitor (OAT-1746) that blocks both extracellular and intracellular Arg activity and has pharmacokinetic properties allowing for administration twice daily. 38,64 We have observed that OAT-1746 completely restores T-cell proliferation suppressed by recombinant Arg1 added to the culture media. Arg1 suppressed T-cell proliferation (online supplementary figure 6), but did not suppress cytotoxicity effector functions of T-cells and NK cells (online supplementary figure 9).…”
Section: Discussionmentioning
confidence: 94%
“…This might be explained by the rapid elimination (the mean residence time was 12.5 min) and high clearance owing to hydroxyguanidine chemical and metabolic lability [ 138 ]. Researches have been investigating new arginase inhibitors with characteristics of low clearance, long t1/2, and moderate volume distribution [ 139 ]. In summary, it is very promising that arginase inhibitor might improve endothelium function and attenuate ischemic heart diseases, but it still needs to be further verified by clinical studies (Tables 2 and 3 ).…”
Section: Arginasementioning
confidence: 99%
“…Recent sulfamoyl and guanidinium Cα-substituted ABH analogs, 3 and 4 respectively, have been developed, with the latter compound revealing higher inhibitory potency against Arg1 and improved pharmacokinetic profile (elimination half-life approx. 1 day) [ 172 ]. Compound 4 was also evaluated regarding its enantiomers, showing greater inhibitory potency (approx.…”
Section: Development Of Arginase Inhibitorsmentioning
confidence: 99%
“…210 times higher) of the R -enantiomer over the S -enantiomer ( Figure 5 ). Nonetheless, tests with the racemic mixture merely doubled the IC 50 when compared to the optimal enantiomeric conformation ( R -enantiomer) [ 172 ], which indicates that extra purification efforts can be skipped, at least for initial proof-of-concept purposes where inactive enantiomers do not affect parallel processes (e.g., if used in trace amounts).…”
Section: Development Of Arginase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation